M Media Audiovisual untuk Motivasi dan Hasil Belajar PJOK Siswa Kelas VII SMP Daniel: Media Audiovisual - Febriyanti Damanik, Frisilia; Vai, Aref; Agust, Kristi (Jurnal Porkes, 2024)
The purpose of this study was to examine how changes in students' cognitive learning outcomes with the basketball PJOK curriculum after using audiovisual learning media. This research method uses classroom action research techniques. The subjects in this study were 20 students, 13 boys and 7 girls. Data collection techniques in this study include observation, tests, and interviews. The research instrument used is a learning observation sheet which contains guidelines in carrying out observations during the learning process. From cycle I to cycle II, the data showed that students' learning activities increased. Students' focus increased from 85% to 95%, the ability to take notes increased from 35% to 70%, the ability to ask questions increased from 10% to 25%, the ability to ask questions increased from 20% to 45%, their participation in class discussions increased from 10% to 30%, and the ability to learn independently increased from 75% to 90%. The percentage of students who completed the learning assessment in both cycles increased from 45% to 80%. With 30% giving very good feedback, 60% giving positive feedback, and 10% giving negative feedback. It can be concluded that motivation, learning outcomes, and student engagement were all positively influenced by the use of audiovisual learning resources.